A Comparative Study Of Coloading And Preloading With Balanced Crystalloids For Prevention Of Post-Spinal Hypotension In Patients Undergoing Elective Caesarean Section (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background Spinal anesthesia is the most common anaesthetic technique for cesarean delivery due to its  rapid onset, a dense neural block, little risk of local anesthetic toxicity and minimal transfer of  drug to the fetus, as well as little risk of failure of block However incidence of hypotension is  one of disadvantages of this technique because of sympathetic blockade. Conventionally,  crystalloid preloading has been used to prevent spinal anaesthesia induced hypotension, but it  has shown varying results. Therefore, focus is on crystalloid coloading for prevention of spinal  induced hypotension.  Method An observational prospective study was done on 60 parturients undergoing elective cesarean  delivery. Patients were randomized into 2 groups who received either crystalloid preloading or  coloading. Parameters assessed were, heart rate, systolic blood pressure, diastolic blood  pressure, mean arterial pressure, incidence of hypotension and use of mephentermine.  Result In this study, there was significant difference in the incidence of hypotension in both the  groups, which was more in preload group. Total dose of mephentermine used was also  significantly more in preload group. Conclusion We concluded that crystalloid coloading is beneficial to prevent post-spinal hypotension in  patients undergoing elective cesarean delivery, as compared to patients receiving preloading  fluid.
Keywords: Crystalloid preload; coload; hypotension